Strategies for delivery of CRISPR/Cas-mediated genome editing to obtain edited plants directly without transgene integration - Kocsisova, Zuzana; Coneva, Viktoriya (Frontiers in Genome Editing, 2023)
Increased understanding of plant genetics and the development of powerful and easier-to-use gene editing tools over the past century have revolutionized humankind's ability to deliver precise genotypes in crops. Plant transformation techniques are well developed for making transgenic varieties in certain crops and model organisms, yet reagent delivery and plant regeneration remain key bottlenecks to applying the technology of gene editing to most crops. Typical plant transformation protocols to produce transgenic, genetically modified (GM) varieties rely on transgenes, chemical selection, and tissue culture. Typical protocols to make gene edited (GE) varieties also use transgenes, even though these may be undesirable in the final crop product. In some crops, the transgenes are routinely segregated away during meiosis by performing crosses, and thus only a minor concern. In other crops, particularly those propagated vegetatively, complex hybrids, or crops with long generation times, such crosses are impractical or impossible.This review highlights diverse strategies to deliver CRISPR/Cas gene editing reagents to regenerable plant cells and to recover edited plants without unwanted integration of transgenes. Some examples include delivering DNA-free gene editing reagents such as ribonucleoproteins or mRNA, relying on reagent expression from non-integrated DNA, using novel delivery mechanisms such as viruses or nanoparticles, using unconventional selection methods to avoid integration of transgenes, and/or avoiding tissue culture altogether. These methods are advancing rapidly and already enabling crop scientists to make use of the precision of CRISPR gene editing tools.